Optimization of Patchouli Oil Extraction Using Microwave-Assisted Extraction: Effect of Particle Size and Power - Nabilah Mukhni Syaviq; Azrifirwan; Omil Charmyn Chatib (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Patchouli (Pogostemon cablin Benth.) oil is Indonesia's flagship essential oil export commodity, yet its extraction faces persistent challenges of low yield, substandard quality, and high energy consumption. This study optimized patchouli oil extraction using Microwave-Assisted Extraction (MAE) through a completely randomized factorial design examining two particle sizes (fine: <5 mm; coarse: 20–50 mm) and two extraction power levels (700 W and 800 W), each replicated three times. Particle size significantly affected oil yield (p = 0.006) and working capacity (p = 0.006), while extraction power showed no significant effect. The coarse particle–800 W combination yielded the highest average yield (4.88%) and the lowest production cost (IDR 8,716.53/ml), while fine particle–800 W achieved the highest patchouli alcohol (PA) content (39.14%). All treatments exceeded the SNI 06-2385-2006 minimum PA requirement of 30%. A regression model was derived: y = 4.657 + 0.040x=0.001x2 (R² = 0.5983). The coarse particle–800 W treatment is identified as the technically and economically optimal condition for MAE-based patchouli extraction. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production